Inovasi Strategi Pembelajaran PAI Untuk Meningkatan Mutu Sekolah Di SD Terpadu Muhammadiyah Kinali - Wahyu Hidayat; Syafruddin Nurdin; Muhammad Kosim; Nisaaul Hanifah (Journal Khafi : Journal Of Islamic Studies, 2024)
Islamic education has important role in the human life that based on Five Basic of the State, because religion is motivation of life and the important tool of development and self-control. Therefore, religion should be known, understood, and practiced by humans in order to be fully human in life. Nowadays, learning of Islamic Education in the school is more focused on formal and memorization (verbal) and theoretical things, not focused on the purpose so forget about the ability to control themselves and how to build faith. Because of it, teachers need to do various innovation in the process of implementation strategy of Islamic Education in the school, in order to improve quality of Islamic Religion that signed by various change both of cognitive, affective, and psychomotor. SD Terpadu Muhammadiyah Kinali has 2 teachers who are all members of the AGPAII organization. They are equipped with understanding and training or workshops in developing the quality of Islamic religious education in schools. so that the teaching and learning process in the classroom is not only focused on the ability to think but also on the realm of affective, and psychomotor